Dichlorido{2-morpholino-N-[1-(2-pyrid-yl)ethyl-idene]ethanamine-κN,N',N''}zinc(II). - Ikmal Hisham, Nurul Azimah; Suleiman Gwaram, Nura; Khaledi, Hamid; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
In the title compound, [ZnCl(2)(C(13)H(19)N(3)O)], the Schiff base ligand acts as an N,N',N''-tridentate chelating agent, making two five-membered rings with the Zn(II) ion. The metal atom is five-coordinated by the Schiff base ligand and two Cl atoms in a distorted square-pyramidal geometry. An intra-molecular C-H⋯Cl inter-action occurs. In the crystal, adjacent mol-ecules are linked together via C-H⋯Cl hydrogen-bonding and long range C-H⋯O and C-H⋯Cl inter-actions into a three-dimensional network.